The city center generating and captive of traffic flows: : case of Constantine - BENAZZOUZ, Imene; GHENOUCHI, Ahmed; LAYEB, Hafid (Journal of Human Sciences, 2019)
The Urban growth has developed in these last years in Constantine, which has led to a strong demand for displacements and an increase in the distances travelled. Despite the creation of a new cities and the development of satellite ones to relieve congestion in the mother city, they remain dependent to downtown for jobs, services and leisure. This last one exerts an attractiveness translated by a pedestrian and motorized mobility (AMM) generating a saturation at the rush hours due to several factors: containing/contents ratio, site Factors, space-functional deployment factors, factors related to the characteristics of the population's displacements. So to better study the mobility phenomenon: we conducted a survey by the hand of using a distribution of a questionnaire of 500 copies (December 2017) and the BETUR-EMA (2012) results were exploted in the form of maps using GIS.